THE ROLE OF FISHERIES EXTENSION IN DEVELOPMENT OF MINA PADI ACTIVITIES IN PAKTIKAH GROUPS OF MINA PADI PAKTIKAH FISH FARMERIN VILLAGE KAMPAI TABU KARAMBIE,SUB-DISTRICT LUBUK SIKARAH, SOLOK CITY, WEST SUMATERA PROVINCE - Selvia Imelda Ellisa; Ridar Hendri; Kusai Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAKThis research was aimed at knowing the role of fisheriesextension and the effectiveness of the extension, and also the problem that faced by the fisheriesextension at Subdistrict Kampai Tabu Karambie. The data of this research was primer and sekunder. The sample of this research was 2 fisheriesextension and 14 member of  minapadi paktikah group. The data is analized by  skala likert and descriptive qualitative. The result of the research shows that the role of the extension as the inisiator, motivator, fasilitator, mediator and supervisor was in good category, it proved by the score 910, it shows that the role of the fisheriesextension to the minapadi paktikah group was delivered well. In the other hand, the effectiveness that being scored by effective, satisfy, adaptation, organization, was in good category with score 437, shows that the fisheriesextension was done their job and understanding by the fish farmer. The problem during this research is the extension was not balance with the group of the fisheries business, so the material was not delivered well. Keywords :Fisheries Extension, Kampai tabu Karambie, Minapadi, Role